The Effect of Using Numbered Heads Together Technique on Reading Comprehension Achievement of the Eight Grade Students at SMP Islam Gumukmas - Martino, Robbica; Istianah, Wiwiek; Ariani, Musli (Universitas Jember, Indonesia, 2015)
This research was a quasi-experimental research using post-test only control group design. The purpose of this research was to know whether or not there was a significant effect of using Numbered Heads Together Technique on reading comprehension achievement of the eight grade students. The research respondents were the students of VIII A and VIII C of SMP Islam Gumukmas. In this research, the students of VIII A were assigned as the experimental group who were taught by using Numbered Heads Together Technique. Meanwhile, the students of class VIII C were assigned as the who were taught by using Lecturing Technique. Before the research was conducted, the researcher had conducted a homogeneity test to know whether the population was homogeneous or not. The result showed that the population was heterogeneous, so the researcher chose the respondents of the research from two classes that had the same or the closest mean difference. The data collection method used was purposive method. There were two kinds of data in this research, primary data and supporting data. The primary data in this research was collected from the students’ reading score. The supporting data was collected by using interview and documentation. The primary data were analyzed using independent sample t- test. The result of the data analysis proved that the application Numbered Heads Together Technique significantly affected the eighth grade students’ reading comprehension achievement. It can be seen from the result of statistical computation value of t-test which was higher than the value of t-table with significant level of 5% (5,37>1,98). This means that the null hypothesis (Ho) was rejected and the alternate hypothesis (Ha) was accepted. Based on the results of hypothesis verification, it can be concluded that there was a significant effect of using Numbered Heads Together Technique on Reading Comprehension Achievement of the Eighth Grade Students at SMP Islam Gumukmas, Jember in the 2014/2015 academic year. Keywords :Experimental Research, Reading Comprehension Achievement, Numbered Heads Together Technique.